Lung recruitment and endotracheal suction in ventilated preterm infants measured with electrical impedance tomography. (26th June 2014) - Hough, Judith L; Shearman, Andrew D; Liley, Helen; Grant, Caroline A; Schibler, Andreas
<x xml:space="preserve">Abstract</x> Aims Although suctioning is a standard airway maintenance procedure, there are significant associated risks, such as loss of lung volume due to high negative suction pressures. This study aims to assess the extent and duration of change in end‐expiratory level (EEL) resulting from endotracheal tube (ETT) suction and to examine the relationship between EEL and regional lung ventilation in ventilated preterm infants with respiratory distress syndrome. Methods A prospective observational clinical study of the effect of ETT suction on 20 non‐muscle‐relaxed preterm infants with respiratory distress syndrome (RDS) on conventional mechanical ventilation was conducted in a neonatal intensive care unit. Ventilation distribution was measured with regional impedance amplitudes and EEL using electrical impedance tomography. Results ETT suction resulted in a significant increase in EEL post‐suction (P < 0.01). Regionally, anterior EEL decreased and posterior EEL increased post‐suction, suggesting heterogeneity. Tidal volume was significantly lower in volume‐guarantee ventilation compared with pressure‐controlled ventilation (P = 0.04). Conclusions ETT suction in non‐muscle‐relaxed and ventilated preterm infants with RDS results in significant lung volume increase that is maintained for at least 90 min. Regional differences in distribution of ventilation with ETT suction suggest that the behaviour of the lung is heterogeneous in nature.